(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kovshar O. V. Specificity of the principle of continuity in teaching of children of preschool and primary school age. The article defines the notion of continuity. It outlines the concept of readiness for teaching preschool children. The role of continuity in organization of education is revealed. The article deals with readiness in social, psychological and intellectual terms. The rapid adaptation of children to learning at school is illustrated.